PENGEMBANGAN VIDEO INTERAKTIF MENGGUNAKAN ARTICULATE STORYLINE 3 PADA MATERI USAHA DAN ENERGI KELAS X SMA - Ramadhani, Indah Sukma; Zulhelmi, Zulhelmi; Syafi’i, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack:Physics is an abstract lesson so that there are manymisconceptions experienced bystudents, especially during the COVID-19 pandemic, especially business and energy materials. Therefore, the purpose of this research is to develop media in the form of interactive video using articulate storyline 3. The research method used is Research and Development (R&D) using the ADDIE model which is only limited to 3 stages, namely the analysis, design, and development stages. The data obtained in the form of the average validation results of three validators. The results showed that the average validation score for all aspects of interactive video media was in the valid category, which was 3.55 and the average result for all aspects of the material was 3.16 with a valid category. So it can be concluded that the learning media in the form of interactive videos on business and energy materials for class X of high school has been valid based on all aspects of both media and material and this interactive video is worthy of being used as a medium for high school physics learning.Keywords: Interactive Video, Articulate Storyline 3, Physics Learning Media